KUALITAS SENSORIS NUGGET AYAM KUB - Restu Hidayah Hidayah; Gama Noor Oktaningrum; Maulida Hena Fatikasari; Subiharta Subiharta (MEDIAGRO, 2021)
KUB chicken is the superior village chicken of the Agricultural Research and Development Agency with egg production reaching 180 eggs/ year. With this advantage, KUB chickens have been cultivated and developed since 2016. In addition to producing quite a lot of eggs, KUB chickens also have delicious meat to eat. One of the most popular processed chicken meat especially for children is chicken nuggets. KUB chicken nuggets were tested for sensory testing including color, texture, aroma and taste for several panelists. The experimental design used in this study was a completely randomized design. The sensory test results showed that KUB chicken nuggets were preferred compared to commercial chicken nuggets. Keywords: KUB Chicken, Nuggets, Sensory quality